2011
DOI: 10.1590/s0101-98802011000200007
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos do butirato nos níveis de peroxidação lipídica em células da mucosa cólica sem trânsito fecal: estudo experimental em ratos

Abstract: Efeitos do butirato nos níveis de peroxidação lipídica em células da mucosa cólica sem trânsito fecal: estudo experimental em ratos

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 40 publications
1
10
0
6
Order By: Relevance
“…13 Based on these findings, several studies began to test the effectiveness of substances with antioxidant activity for the treatment of DC. 19,[30][31][32] The results of these studies confirmed that natural or synthetic substances with antioxidant activity were able to reduce the production of OFR and to improve the histological changes that characterize DC. 19,[29][30][31][32] Riley et al in 1989 33 were the first to demonstrate the benefits of using enemas with SCF in the acute phase of ulcerative rectitis.…”
Section: Discussionsupporting
confidence: 56%
“…13 Based on these findings, several studies began to test the effectiveness of substances with antioxidant activity for the treatment of DC. 19,[30][31][32] The results of these studies confirmed that natural or synthetic substances with antioxidant activity were able to reduce the production of OFR and to improve the histological changes that characterize DC. 19,[29][30][31][32] Riley et al in 1989 33 were the first to demonstrate the benefits of using enemas with SCF in the acute phase of ulcerative rectitis.…”
Section: Discussionsupporting
confidence: 56%
“…A series of studies confirmed that the irrigation of segments without fecal stream with SCFAs-rich solutions, particularly butyrate, can revert endoscopic and histological alterations related to the disease and reduce the levels of tissue oxidative stress [9][10][11][12][13]15,17,18,33,34 . The main action of SCFAs in the segment without fecal stream would be to restore homeostasis in the reactions that promote energy production by the cells, preventing the excessive formation of OFRs and, consequently, the tissue oxidative stress 34 . When considering that the use of substances with antioxidant activity can neutralize the harmful effects of OFRs, it becomes an interesting strategy for the treatment of diseases related to oxidative stress.…”
Section: Discussionmentioning
confidence: 91%
“…Studies have shown that fecal stream restoration reverts the disease symptoms in most cases, making it the most effective therapy for the prevention of DC 13 .However, fecal traffic recovery is not always possible, which promotes the evaluation of other therapeutic strategies 20 . As the pathogenesis of DC is related to deficient supply of SCFAs, the most obvious strategy is to apply enemas with SCFAs in the segment without fecal stream 18,19,33,34 . A series of studies confirmed that the irrigation of segments without fecal stream with SCFAs-rich solutions, particularly butyrate, can revert endoscopic and histological alterations related to the disease and reduce the levels of tissue oxidative stress [9][10][11][12][13]15,17,18,33,34 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations